2020
DOI: 10.1029/2019jc015891
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Intraseasonal Oscillations in the Indian Ocean Using Satellite Observations

Abstract: Intraseasonal oscillations (ISOs) in the Indian Ocean play a significant role in determining the active (wet) and break (dry) cycles of the southwest monsoon rainfall. In this study, we use satellite‐derived precipitation, sea level anomalies (SLAs), sea surface salinity (SSS), sea surface temperature, and surface winds to monitor the 30‐90‐day, 10‐20‐day, and 3‐7‐day ISOs, and how they influence local dynamics. The main focus of this work, however, is showing the importance of using SLA and SSS to monitor ISO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 83 publications
(227 reference statements)
4
27
0
Order By: Relevance
“…These altered CKW patterns are consistent with previous studies (Rao et al, 2010; Roman‐Stork, Subrahmanyam, & Trott, 2019), which suggested that a strong pIOD could weaken the CKWs in the Bay to the point of reversing their sign, as seen in 2019. This has serious implications for freshwater transport into the southeastern Arabian Sea by the EICC, which is typically modulated by the second downwelling Kelvin wave and which is a major contributor to SW monsoon onset (Roman‐Stork, Subrahmanyam, & Trott, 2019; Roman‐Stork, Subrahmanyam, & Trott, 2020). The Rossby waves radiated by these Kelvin waves also work to excite eddying in the western Bay the following season (Chen et al, 2012; Rao et al, 2010; Sreenivas et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These altered CKW patterns are consistent with previous studies (Rao et al, 2010; Roman‐Stork, Subrahmanyam, & Trott, 2019), which suggested that a strong pIOD could weaken the CKWs in the Bay to the point of reversing their sign, as seen in 2019. This has serious implications for freshwater transport into the southeastern Arabian Sea by the EICC, which is typically modulated by the second downwelling Kelvin wave and which is a major contributor to SW monsoon onset (Roman‐Stork, Subrahmanyam, & Trott, 2019; Roman‐Stork, Subrahmanyam, & Trott, 2020). The Rossby waves radiated by these Kelvin waves also work to excite eddying in the western Bay the following season (Chen et al, 2012; Rao et al, 2010; Sreenivas et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The 3-7-day mode, composed of synoptic disturbances and oscillations in the monsoon trough, is a primary contributor to the active and break cycles in the monsoon (Goswami et al, 2003;Subrahmanyam et al, 2020). With the monsoon system being a highly coupled phenomenon, a number of studies have focused on the atmospheric implications of these 3-7-day ISOs (Gadgil & Asha, 1992;Gadgil & Joseph, 2003;Goswami & Ajaya Mohan, 2001;Goswami et al, 2003;Krishnamurti & Bhalme, 1976;Murakami, 1976;Rajeevan et al, 2010;Singh & Nakamura, 2010), and some more recent studies have observed the oceanic response to these oscillations (Goswami et al, 2016;Roman-Stork, Subrahmanyam, & Trott, 2020;Subrahmanyam et al, 2020); however, there remains a gap in the knowledge as to how mesoscale eddies could be in turn influencing these synoptic oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…This length scale is crucial, as it means that SMAP, that has a 1,000 km swath, is able to capture the structure of the 3‐7‐day mode. By comparison, altimeters have a much narrower swath and so are not able to capture the signal as clearly (Roman‐Stork et al, 2020b).…”
Section: Resultsmentioning
confidence: 99%
“…There have been a number of studies regarding the active and break phases of the monsoon (Gadgil & Asha, 1992;Gadgil & Joseph, 2003;Goswami & Ajaya Mohan, 2001;Goswami et al, 2003;Krishnamurti & Bhlame, 1976;Murakami, 1976;Rajeevan et al, 2010;Singh & Nakamura, 2010), but most have been focused on the atmospheric aspect, with little, if any, consideration given how this would impact the upper ocean. As the monsoon system is a highly coupled phenomenon, it remains critically important that we understand how these atmospheric processes are translated into the ocean and how the ocean in turn influences these atmospheric processes (Goswami et al, 2016;Roman-Stork et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…The MJO is an eastward-propagating system with a phase speed of roughly 5 m/s that is characterized by alternating bands of suppressed and enhanced convection over the equator [9][10][11][12][13]. While it operates on a 30-90-day timescale, it is closely related to the 30-60-day boreal summer intraseasonal oscillation (BSISO), which is a northward-propagating phenomenon in the northern Indian Ocean that has been known to heavily impact monsoon precipitation and onset [13][14][15][16]. The MJO is the dominant form of intraseasonal variability in the tropics [12,13] and is widely known to impact cyclogenesis on a global scale [5,17,18].…”
Section: Introductionmentioning
confidence: 99%